Kinanthropometry and exercise physiology - Eston, Roger G.; Norton, Kevin (Routledge Taylor and Francis Group, 2019)
Fully updated, revised and consolidated into one single volume, the fourth edition of Kinanthropometry and Exercise Physiology offers the best theoretically contextualised, practical resource for instructors and students available. Incorporating substantial sections on kinanthropometry, exercise physiology, energy systems and the application of science in health and high-performance settings, the book covers the basics of measurement in exercise science through to advanced methods, and includes brand new chapters on: Pre-exercise screening and health risk stratification; Functional movement assessment; Point of care testing; Anthropometry standards; Anaerobic power and capacity; History of exercise for health benefits; Monitoring training loads in high-performance athletes; Measuring game style in team sports. Offering on-line access to newly developed exercise science measurement tools through the Exercise Science Toolkit - www.exercisesciencetoolkit.com - no other book offers such a complete resource, from the science of kinanthropometry and exercise physiology to their applications in health and performance, through practical, interactive learning. This book is an essential companion for students on any sport and exercise science-related degree programme an any instructor leading practical, laboratory-based classes